Jövőt formáló nyelvi nevelés - Kontra Miklós; Контра Міклош (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2023)
A magyar standard nyelvi ideológia, annak átörökítése és fenntartása azért nagyon káros, mert fenntartja a nyelvi alapú társadalmi egyenlőtlenséget és ezáltal jelentősen csökkenti a nemzet erőforrásait is. A „helyes magyar beszéd” nemzeti elvárása – vagyis, hogy minden magyar ember beszélje anyanyelvét „helyesen” – egyrészt irreális elvárás, másrészt hatalmas társadalmi károkat okoz. Az irreális elvárásokat számos tudományos vizsgálat eredményeivel mutatom be, s a társadalmi károkat is jól dokumentált esetekkel illusztrálom. E helyzetből kiút lehet a „helyes – helytelen” minősítések kiiktatása és a „helyénvaló – nem helyénvaló” minősítések meghonosítása. Az iskolákból el kell távolítani a felcserélő nyelvpedagógiát s be kell vezetni a hozzáadót. A tanárképzés megváltoztatásánál is jóval nagyobb feladatunk a kultúraváltás: az egész magyar nyelvi közgondolkozás megváltoztatása úgy, hogy a mostanit kiiktatjuk és helyette elterjesztünk egy demokratikusabb és a nyelvi változatokat nem kiirtó, hanem tisztelő és értékelő közbeszédet.

Abstract. The transmission and maintenance of Hungarian standard language ideology is extremely harmful socially because it perpetuates social inequity and reduces the nation's resources. The insistence on speaking Hungarian “correctly”, i.e., that all Hungarians speak their mother tongue “correctly”, is both unrealistic and socially extremely damaging. In addition to anecdotal evidence cited from belletristic authors Gyula Illyés (1930s), Szilárd Borbély (21st century) and others, the results of several sociolinguistic studies are cited to show how unrealistic such expectations are. These studies cover important sociolinguistic variables e.g., t-final verbs and the inessive case ending (bVn) as used by Hungarians in Hungary, in Transcarpathia (Ukraine) and in Transylvania (Rumania). The social harms that result are illustrated by several well-documented cases of linguicism. The author recommends that the evaluation of linguistic phenomena in terms of “correct – incorrect” should be abandoned and replaced by “appropriate – inappropriate” evaluations (where appropriate language use varies according to speech partners and speech situations). The subtractive language education prevalent in Hungarian schools should be replaced by additive education. Teacher training should be revamped similarly, but the most difficult task ahead is changing the culture of widespread belief in “correct Hungarian” and cultivating a more democratic language ideology which, rather than striving to eliminate language variation, respects linguistic varieties and their speakers.

Резюме. Ідеологія угорської стандартної мови, її передача та підтримка є дуже шкідливими, оскільки вона підтримує соціальну нерівність, засновану на мовній основі, і тим самим значно зменшує ресурси нації. Національне очікування «правильного угорського мовлення», тобто того, що всі угорці «правильно» володіють рідною мовою, є нереальним очікуванням, з одного боку, і завдає величезної соціальної шкоди, з іншого. Нереалістичні очікування презентую результатами численних наукових досліджень, а також проілюструю соціальну шкоду добре задокументованими випадками. Виходом із ситуації, що склалася, є скасування оцінювань «правильно – неправильно» та запровадження — «доречно – невідповідно». Дублюючу мовну педагогіку необхідно вилучити зі шкіл і запровадити адитивну (доповнюючу). Наше завдання набагато складніше, ніж змінити підготовку вчителів, маємо змінити культуру: змінити всю мовну громадську думку в Угорщині, усунувши нинішню й натомість поширивши демократичний публічний дискурс, який не викорінює мовні варіанти, але поважає та цінує їх.
Changing Hungarians' L1 education
Мовна освіта формує майбутнє
https://aab-philologica.kmf.uz.ua/aabp
Keywords: standard nyelvi ideológia; „helyes” magyar beszéd; társadalmi károkozás; hozzáadó nyelvpedagógia; kultúraváltás